Letter (copy) : Spanish Refugee Children - Tewson, Vincent
1939-10-30 038-0062-002 -2- remain, but I do know that in several cases the Basque children have been evacuated together with the British children. I trust that this infomation will meet your requirements. Yours sincerely, Assistant Secretary. 292/946/38/62(II)